Copper‐Catalyzed CNH2 Arylation of 2‐Aminobenzimidazoles and Related C‐Amino‐NH‐azoles. Issue 13 (7th June 2016) - Rao, Desaboini Nageswar; Rasheed, Sk.; Kumar, Karampoori Anil; Reddy, Annem Siva; Das, Parthasarathi
Abstract: A copper(II)‐catalyzed selective CNH2 arylation of 2‐aminobenzimidazoles and related C‐amino‐NH‐azoles was achieved in presence of 2, 2′‐bipyridine and cesium carbonate at 60 °C under open air conditions and this is first method for the copper‐catalyzed selective CNH2 arylation in the presence of other reactive nucleophilic sites. Previously unexplored heteroaromatics possessing multiple nucleophilic sites that are selectively arylated at the CNH2 position are obtained, providing an exceptional tool for rapid delivery of a diverse array of medicinally important CNH(aryl) derivatives of aminoazoles without any protection/deprotection of ring NH bonds. It is first example for the selective CNH2 arylation of 5‐aminoindazole, 4‐aminopyrazole, 5‐aminopyrazole, 9 H ‐purine‐6‐amine, and 1 H ‐pyrazolo[3, 4‐ d ]pyrimidin‐4‐amine derivatives. Abstract :